The relationship between public expenditure, corruption and poverty in Nigeria - Dankumo, Ali Madina; Ishak, Suryati; Bani, Yasmin; Hamza, Hanny Zurina (Universitas Negeri Malang, 2019)
Poverty in Nigeria affects about 67% of the population who have insufficient means of supporting their families. World Food Programme have spent $126million on food assistance in Nigeria, yet majority are hungry. Government, through its expenditures, provided public goods to improve welfare and reduce poverty, but all is to no vail because it is mostly affected by bureaucratic bottlenecks and corruption. This paper investigated the long-run consequence of corruption in a model of public expenditures and poverty in Nigeria, to test the hypothesis of “grease or sands the wheels”. The sources of data were; Central Bank of Nigeria, National Bureau of Statistics Nigeria, and World Bank for 21 years (1996-2016). The study employed the ARDL bounds test. The findings revealed a long-run relationship between public expenditures, corruption and poverty. The aspect of expenditures on economic sector is significant, while that of social sector is not. Corruption is positively related to poverty, this is despite increase in corruption index, which remains below 30% (still corrupt since it’s less than 50%), hence, making the public expenditure not to impact on poverty, sanding the wheels. The study suggested some measures to enhance corruption index thereby allowing public expenditure to impact on poverty.